Signalling in Neutrophils: A Retro Look. (7th November 2013) - Naccache, Paul H.
Abstract : This review presents a summary of signalling events related to the activation of human polymorphonuclear neutrophils by a variety of soluble and particulate agonists. It is not intended as a comprehensive review of this vast field or as a presentation of the multiple new aspects of neutrophil functions that are being documented at an ever faster rate. Its aim is rather to focus on multiple aspects of major signalling pathways that, in the view of this reviewer, are currently shadowed by present trends and to provide the core evidence for their implication and the limitations of our present knowledge. More specifically, this review starts with cell surface receptors and some of their functional and biological properties and then moves on to downstream transducers (G proteins) and effectors (the phosphoinositide, tyrosine kinases, and cyclic nucleotide pathways). Classical second messengers (calcium, protein kinase C, polyphosphoinositides, and cyclic nucleotides) are emphasized. It is hoped that this presentation will not only remind present-day investigators of the central role these pathways play in the regulation of the functional responsiveness of neutrophils, but that it will also highlight some of the areas deserving additional investigation.